Chaotic image encryption algorithm based on single image local scrambling and dynamic feedback diffusion - Yeqin CUI; Guochao DING (Dianxin kexue)
A novel chaotic image encryption algorithm based on single image local scrambling and dynamic feedback diffusion was presented.Firstly,a single image local scrambling algorithm was proposed.Secondly,a novel dynamic feedback diffusion strategy was proposed to change the pixel values of the scrambled image in the phase of diffusion,by which improved the results of image encryption.Finally,the simulation results and performance analysis show that the number pixels change rate（NPCR）values and unified average changing intensity（UACI）values of the proposed algorithm can be close to 99.6% and 33.4%,showing that the proposed algorithm has better resistance to differential attacks and saves time compared with the other three classic algorithms.